SOME REGULARITIES OF THE UNCERTAIN SYSTEMS ROOT LOCUS PORTRAITS - A. A. Nesenchuk (Системный анализ и прикладная информатика, 2014)
The paper is aimed at investigation of dynamic properties of control systems with interval parametric uncertaint y, which dynamics is described by the family of interval characteristic polynomials. The mathematical model of the system  is considered in the form of root locus portrait, represented by the root locus fields family. Asymptotic properties,  peculiarities and regularities of the interval systems root locus portraits configuration (location of their branches, initial points and asymptotes) are being discovered.